The role of family planning counselling during maternal and child health services in postpartum modern contraceptive uptake in Ethiopia: A national longitudinal study - Mruts, Kalayu; Tessema, Gizachew; Gebremedhin, Amanuel; Scott, Jane; Pereira, Gavin (2022)
Family planning counselling can help improve the postpartum modern contraceptive uptake. However, studies in Ethiopia indicate inconsistent effects of integrated family planning counselling on postpartum modern contraceptive uptake. This study aimed to determine the extent of family planning counselling and its role in improving postpartum contraceptive uptake among women in Ethiopia. We used the Performance Monitoring for Action (PMA) Ethiopia panel survey data, a community-based prospective cohort study. Randomly selected pregnant women were recruited at the baseline interview and followed by six weeks and six months postpartum. A weighted generalised linear model fitted with a Poisson distribution and a log link function was used to estimate the adjusted relative risk (aRR) and 95% Confidence Interval (CI) of modern contraceptive uptake. The coverages of family planning counselling provision during ANC, prior to discharge and child immunisation were 20%, 27% and 23%, respectively. The modern contraceptive uptakes by six weeks and six months postpartum were 18% and 36%, respectively. Family planning counselling prior to discharge from the facility was associated with increased modern contraceptive uptake by six weeks (aRR 1.25; 95% CI 0.94, 1.65) and six months postpartum periods (aRR 1.07; 95% CI 0.90, 1.27). Moreover, women who received family planning counselling during child immunisation were 35% more likely to use modern contraceptives by six months postpartum (aRR 1.35;95% CI 1.12, 1.62). However, counselling during ANC visits was not associated with modern contraceptive uptake by either six weeks or six months postpartum. A significant proportion of women had missed the opportunity, and the postpartum modern contraceptive uptake was low. Despite these, family planning counselling prior to discharge from the facility and during child immunisation improved the postpartum modern contraceptive uptake. However, our finding revealed insufficient evidence that family planning counselling during ANC is associated with postpartum modern contraceptive uptake.